FULFILLING URBAN INFRASTRUCTURE STANDARDS TO INCREASE THE CARRYING CAPACITY OF TOURISM DESTINATION - Fatina, Shana; Soesilo, Tri Edhi Budhi; Tambunan, Rudy Parluhutan (UI Scholars Hub, 2023)
Labuan Bajo is an emerging coastal tourism destination in Indonesia, which is also part of the United Nations Educational, Scientific and Cultural Organization (UNESCO) Komodo Biosphere Reserve located in the East Nusa Tenggara region. Recent tourism developments have transformed Labuan Bajo from a rural area into an urban area, and significant land use changes have followed. This new urban area development will attract tourists as well as population migration. The ongoing issue is to develop the urban infrastructure and facilities of Labuan Bajo in an integrated and sustainable way, considering the carrying capacity following the high demand for tourism and migration. This study investigates the transition pattern from rural to urban areas on coastal tourism. It calculates existing carrying capacity based on the availability of attractions in Labuan Bajo tourism as a coastal destination, including the Komodo National Park area. The study results in Labuan Bajo's carrying capacity have yet to exceed its limit calculated based on the number of existing visitors and as projected in the tourism master plan. However, Labuan Bajo has already shown the urban typology characteristics required to transform the sub-district into a small city. Tourist visits must be distributed outside the Komodo National Park area and to other destinations in the East Nusa Tenggara archipelago to balance the growth and impact of tourism and its supply chain. Environmental, economic, and sociocultural carrying capacity shall be considered in destination management to guarantee measurable sustainable tourism practices in the long run.